Sistem Informasi Manajemen Pelaporan Hasil Kerja Cleaning Service - Novrian Eka Cahya; Irfan Mahendra (Prosiding, 2025)
In the digital era, fast, accurate, and structured work result recording has become essential for cleaning service companies to maintain operational performance and service quality. This study aims to design and implement a web/mobile-based management information system for reporting cleaning service performance, addressing issues of manual recording such as data inaccuracy, monitoring difficulties, and delays in report generation. The development method applied was the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and literature review, while the system was tested using black-box testing on all main features. The test results showed that all test scenarios (login, report input, supervisor verification) achieved a "Match" status or a 100% success rate, demonstrating that the application works as intended. The system effectively accelerates the reporting process, improves recording accuracy, and facilitates supervisors in verifying and compiling reports. Its implementation at PT. Sarana Steel has made a tangible contribution to enhancing operational efficiency and transparency in cleaning service performance, serving as a model solution for similar companies